2018
DOI: 10.15171/ijhpm.2018.75
|View full text |Cite
|
Sign up to set email alerts
|

Complex Leadership in Healthcare: A Scoping Review

Abstract: Background: Nowadays, health systems are generally acknowledged to be complex social systems. Consequently, scholars, academics, practitioners, and policy-makers are exploring how to adopt a complexity perspective in health policy and system research. While leadership and complexity has been studied extensively outside health, the implications of complexity theories for the study of leadership in healthcare have received limited attention. We carried out a scoping review of complex leadership (CL) in healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 73 publications
2
89
0
3
Order By: Relevance
“…He also disciplined the space by using an agenda to systematise the processes in the meeting and drew on distributed leadership to create an environment that reinforced the overall goal (64). As these experiences demonstrate, complexity-sensitive managers adopt a contingency approach to leadership, balancing transactional, transformational and distributed leadership styles based on the needs, the situation and the problem at hand , adapting leadership practices as required in particular contexts (36). A study on the daily management practices of sub district managers in South Africa found, for example, that improving practices in daily routines, such as facilitation styles in meetings, minute taking, etc.…”
Section: Sensegiving and Social Sensemakingmentioning
confidence: 99%
See 3 more Smart Citations
“…He also disciplined the space by using an agenda to systematise the processes in the meeting and drew on distributed leadership to create an environment that reinforced the overall goal (64). As these experiences demonstrate, complexity-sensitive managers adopt a contingency approach to leadership, balancing transactional, transformational and distributed leadership styles based on the needs, the situation and the problem at hand , adapting leadership practices as required in particular contexts (36). A study on the daily management practices of sub district managers in South Africa found, for example, that improving practices in daily routines, such as facilitation styles in meetings, minute taking, etc.…”
Section: Sensegiving and Social Sensemakingmentioning
confidence: 99%
“…This has resulted in the development of many managerial competency frameworks (28)(29)(30)(31) and the delineation of the twelve practices of managers, grouped as (1) leading (2) managing (3) and governing (13). Over time, as the DHS has come to be recognised as a complex adaptive system (CAS) (32)(33)(34), understanding of the competencies and capabilities that district managers need has evolved (10,(35)(36)(37)(38). As a result, capacity development efforts have moved beyond a traditional focus on administrative management and health professional practice training.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement of FLNMs is central to the development of structures and cultures to improve patient safety and achieve sustained quality in nursing care [1]. There is growing awareness of the complexity perspective in healthcare among scholars, academics, practitioners, and policy-makers [7] and of how different types of leadership influence outcomes [8]. Within healthcare generally and QI work specifically, adaptive leadership that regards human interaction [9] and is responsive, flexible, and open to change [4], seems to be more useful than leadership based on control [4].…”
Section: Introductionmentioning
confidence: 99%